If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -2 + 9y = 6 Reorder the terms: -2 + 9y + 9y = 6 Combine like terms: 9y + 9y = 18y -2 + 18y = 6 Solving -2 + 18y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 18y = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 18y = 6 + 2 18y = 6 + 2 Combine like terms: 6 + 2 = 8 18y = 8 Divide each side by '18'. y = 0.4444444444 Simplifying y = 0.4444444444
| 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 | | 3(xy+w*w)+2xy-2w*2w= | | 9w-18+5w+2=180 | | 9.5+p-6.8=7.3 | | -5s+9=-6 | | (5y+5)-5y=5 | | 15g-3(4g-6)=3g+9-9g | | 6+2x=4x-2 | | 2x+1=10x-3(x-1) | | 3y^2-15y=12 | | x^2+x-80=0 | | 6y+7=5y-5 | | 4a+2b-3-6a-5b= | | 5.5y=71.5 | | 7-6a=7a | | -3(4y-2)-y=-3(y-5) | | -2x^2+6x+8=0 | | 3x+2(x+3)=31 | | 14x-(4+5x)= | | (-11)-18= | | 2x+5(x-4)=36 | | 4(xy)=(4y) | | 6+10(15)= | | 4x+11=-12x-37 | | 6n^2-21n-15=0 | | (W-5)(2w+7)= | | 3x+3(x-2)=30 | | 10x+8=3(3x+1) | | 9x+7(-x-10)+14-3x= |